Berit Olam: Isaiah 56-66 - Niskanen, Paul (Book collections on Project MUSE., 2014)
"This multi-volume commentary reflects a relatively new development in biblical studies. The readings of the books of the Hebrew Bible offered here all focus on the final form of the texts, approaching them as literary works, recognizing that the craft of poetry and storytelling that the ancient Hebrew world provided can be found in them and that their truth can be better appreciated with a fuller understanding of that art." --from back cover.